MENINGKATKAN KEMAMPUAN MENYIMAK MELALUI METODE BERCERITA DENGAN BIG BOOK PADA ANAK USIA 5- 6 TAHUN DI TK CAHAYA HATI KECAMATAN KAMPAR KABUPATEN KAMPAR - Herlina, Herlina; Zulkifli, Zulkifli; Chairilsyah, Daviq (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This study aims to determine the increase capability meyimak the children in group B through storytelling with big book in kindergarten Light Kampar District Kampar district. This study is the kind of research that menggunakann action research or (PTK) is conducted in two cycles. Each cycle consists of planning, action planning, observation / evaluation and reflection. Subject empirically n are 15 children in the kindergarten group B light. The research data obtained through observation and data analysis were conducted by using descriptive analysis of quantitative and qualitative. The results showed that storytelling with Big Book can improve the listening skills of children in group B. It Dapa t be seen from the increase in the average percentage of listening skills of children in the first cycle is 45% undeveloped den gan criteria (M B) and an increase of 58.84% in the second cycle be 71.48% with developing criteria to expectations (BSH). So, storytelling with a big book d apat improve listening skills in 5-6 years old children in kindergarten Light Kampar District Kampar regency.Keywords : Listening ability, Storytelling Method With Big Book